Estratégias de polidez linguística na realização do ato de fala aconselhar : um estudo contrastivo entre falantes nativos e não nativos de inglês - Ferreira, Gustavo Reges (2015)
Research in the field of cross-cultural Pragmatics indicate that a learner with a high level of grammatical proficiency does not necessarily present an equivalent pragmatic development. Thomas (1983) alerts us to the seriousness of pragmatic failure by stating that “a speaker who is not operating according to the standard grammatical code is at worse condemned as 'speaking badly', the person who operates according to differently formulated pragmatic principles may well be censured as behaving badly; as being an untruthful, deceitful, or insincere person” (THOMAS, 1983, p. 107). Aiming at contributing to the study of pragmatic aspects in the Brazilian English language teaching context our research was dedicated to the realization of a contrastive study. The realization of a contrastive study like ours is justified in the fact that many English language students have the desire to either visit an English speaking country and / or study in an English speaking country. Therefore, we believe it is part of the responsibility of English teachers to approach in the classroom not only structural, but also pragmatic aspects of the target language. Our study compares and describes the use of politene strategies in the realization of the speech act of advising by two English-speaking groups, one composed of native English speakers and the other composed of non-native English speakers, both in the same situation. Both groups were composed of 15 individuals aged between 22 and 58, of both sexes 7 men and 8 women. The native English speakers were of American nationality and the non-native group were Brazilians who never lived in an English speaking country. Our research is based on the speech act theory (AUSTIN, 1962; Searle, 1969, 1975) and the politeness theory (BROWN AND LEVINSON, 1987). Our research hypothesizes that when performing the speech act of advising non-native speakers are more direct, showing a less attenuated speech when compared to the speech of the English native speakers. For data analysis we used Martinez-Flor’s taxonomy (2005) and Brown and Levinson’s positive and negative politeness strategies as well. Results suggest that in comparison to native English speakers the use of strategies by non-native English speakers is less diversified.